Qat’I Dan ZAnni Dalam Pemikiran Islam (Memahami Teks Dan Konteks Secara Proporsional) - Mohammad Mufid (Universitas Islam Negeri Alauddin, 2014)
Term qat’i was at first used in 4th H. It was used in as-Shairafi (w. 330 H.) and al-Jasshash (w.370 H.) era. Both of them are mentioned as the first pioners who popularized term of qat’i. Eventhough, implicitly, as-Syafi’i had mentioned this terms in his book al-Risalah, which had lived long time ago before the era of as-Shairafi and al-Jashshash. The concept of qat’i and zanni were not the final concepts. It is opened to be elaborated. According to Masdar F. Mas’udi, the term qat’i is defined as the universal concept and passed through the dimension of time and space (mutlaq). While zanni ia regarded as religious guindance from both al-Quran and Hadis that constitutes the breakdown of the principles of Muhkam texts. The implication of the elaboration consept (qat’i and zanni) has opened the space of ijtihad to the text of qat’i in rank of practice (tatbiq). Along this time, the domain of ijtihad was limited to the text of zanni or it is minimally used when there is no solutions in text of qat’i. Nevertheless, it must be remembered that not all text of qat’i must be comprehended (ijtihad) absolutely. But in other ways, it is limited to qat’i fi ba’di al-ahwal or it pertains qat’I nas restrictively.